Medical Milestone, Millennial Mission - Ramírez de Arellano, Annette B. (Puerto Rico Health Sciences Journal, 2009)
Clean water is a major medical milestone, and has so been considered in a survey conducted by the British Medical Journal. This historical note describes the early struggles leading to the sanitary revolution in Europe, and the efforts of Edwin Chadwick to convince others of the importance of clean water. The goal of clean water remains unfulfilled in many parts of the world.